Pneumonia causing bacterial leading to facial abscess in a doe: a case report - Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Sadiq, Muhammad Abubakar; Abba, Yusuf; Tijjani, Abdulnasir; Mohammed, Konto; Osman, Abdinasir Yusuf; Mohd Lila, Mohd Azmi; Haron, Abdul Wahid; Saharee, Abdul Aziz (ScopeMed Publishing, 2015)
An adult Jamnapari-cross doe managed in an intensive, raised-house farm was presented with the primary complaint of left facial swelling. The swelling was approximately 8cm x 15cm with soft, fluidfilled consistency and warm upon palpation. There were also mucoid discharge from both nostrils and mild crackle sound upon lung auscultation. The doe was diagnosed to have pneumonia together with facial abscess where the causative agent was a mix infection. The doe was administered with 2.2mg/kg Flunixin meglumine and Norodine 24 1ml/16kg intravenously, followed by abscess lancing. A ring-block was performed by infiltrating lidocaine hydrochloride 2% around the swelling site, followed by fine needle aspiration (FNA). The pus aspirated was sent for bacteriological culture, which yielded a mixed growth of Arcanobacterium haemolyticum and Mannheimia haemolytica infection. Excessive bleeding resulted from the lancing procedure was countered with cauterization using heated scalpel blade holder, administration of 1ml Vitamin K intravenously and 3ml via topical flushing. Oxytetracycline 20mg/kg was also dispensed for topical flushing at the abscess pocket.